2011
DOI: 10.1097/aud.0b013e3181f46a17
|View full text |Cite
|
Sign up to set email alerts
|

Mean Hearing Thresholds Among School Children in Taiwan

Abstract: These results indicate that the mean thresholds among the study sample were well above (meaning poorer) the pure-tone average of 15 dB HL, as recommended in a previous study. Therefore, the results of this study suggest the need to further determine the etiology of hearing loss among children in grades 1, 4, 7, and 10 in the Datong and Jhongshan Districts of Taipei City and perhaps Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…One of the most striking findings was the lack of articles estimating the true prevalence of hearing loss among school children. Although 17 articles included prevalence estimates, ranging from 0.9% in Taiwan 55 to 34% in Brazil, 62 many other articles provided referral percentages of screening tests in lieu of prevalence † . These studies assumed 100% sensitivity in their screening protocols and did not include a comparison with gold standard pure tone audiometry, meaning that any estimates on disease prevalence represented screening test referral percentages rather than true measures of disease prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most striking findings was the lack of articles estimating the true prevalence of hearing loss among school children. Although 17 articles included prevalence estimates, ranging from 0.9% in Taiwan 55 to 34% in Brazil, 62 many other articles provided referral percentages of screening tests in lieu of prevalence † . These studies assumed 100% sensitivity in their screening protocols and did not include a comparison with gold standard pure tone audiometry, meaning that any estimates on disease prevalence represented screening test referral percentages rather than true measures of disease prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwanese children (Yang et al 2011) the threshold levels are the highest of all studies (Table 4). They show only small, age-dependent improvements between -0.1 dB at 4 kHz and -1.1 dB at 500 Hz.…”
Section: Discussionmentioning
confidence: 93%
“…High levels of tympanometric alterations have been previously reported in the literature and corroborate our finding regarding the high prevalence of conductive alterations. However, the tympanometric curve is used as the pass criterion rather than the tympanometric gradient 10,19,30,31 , although this measure may be useful in detecting otitis media with effusion (OME). A study comparing children and adolescents with and without OME found, in the former group, gradient values between 0.01 and 0.93 ml 32 , thus agreeing with the 0.2 ml criterion we adopted in this study as a signal of hearing screening failure.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of each type of hearing loss found in the study Labels: transient evoked otoacoustic emissions -TEOAE Results of the different hearing screening protocols dB normality criterion, found a 24.6% prevalence of hearing loss in the sample31 . Despite differences in criteria, this value is similar to that found in the present study.…”
mentioning
confidence: 90%